Trophic structure of freshwater food webs (Zoological Records and Reviews, 2024)
Freshwater food webs are among the most structurally complex and ecologically sensitive systems in continentalecosystems, yet comparative analyses of trophic organisation across lake and river types remain limited. This studycharacterises the trophic structure of eight freshwater food webs--four lakes and four rivers--spanning oligotrophic tohypertrophic conditions across the Netherlands and Finland, using stable isotope analysis (delta13C and delta15N)combined with stomach content analysis and quantitative macroinvertebrate and fish sampling (n = 1,842 individualorganisms across 112 taxa). Trophic level assignments based on delta15N (trophic enrichment factor 3.4 per mille perlevel) revealed food chains of 3.8-5.2 trophic levels across systems, with hypertrophic lakes supporting shorter, morecompressed chains (mean 3.9 +- 0.3 TL) than oligotrophic lakes (mean 4.8 +- 0.4 TL; Mann-Whitney U, p = 0.004).Connectance ranged from 0.08 to 0.19 across food webs, negatively correlated with species richness (r = -0.74, p =0.034). Omnivory index values were significantly higher in river food webs (mean 0.31 +- 0.06) compared to lakes (0.19+- 0.05; t(6) = 3.28, p = 0.017), consistent with the greater hydraulic variability of lotic systems promoting generalistfeeding strategies. Stable carbon isotopes identified pelagic algal and benthic periphyton pathways as approximatelyequal contributors to riverine energy flow, whereas lake food webs were predominantly (71-89%) subsidised by pelagicproduction. These results demonstrate systematic structural differences between lentic and lotic freshwater food webswith direct implications for bioassessment and eutrophication management under the EU Water Framework Directive.
Keywords: EU Water Framework Directive; eutrophication; omnivory; connectance; freshwater ecology; delta13C; delta15N; trophic level; stable isotope analysis; food web